2021
DOI: 10.38042/biotechstudies.932376
|View full text |Cite
|
Sign up to set email alerts
|

Role of Grafting in Tolerance to Salt Stress in Melon (Cucumis melo L.) Plants: Ion regulation and antioxidant defense systems

Abstract: Grafting in vegetables is a method that has been commonly used in recent years, not just for the treatment of soil borne diseases and pests, but also to facilitate higher abiotic stress tolerance under conditions such as salinity. Herein, it was aimed to determine if the salt tolerance of two salt-susceptible melon genotypes, SCP-1 and SCP-2, could be improved by grafting onto TLR-1 and TLR-2, which are salt-tolerant melon genotypes, and Albatros commercial melon rootstock. The grafted plants were grown in pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 39 publications
0
3
0
1
Order By: Relevance
“…In their role against drought and salinity stresses, it has been suggested that the Aquaporins regulated changes in the root, stem and leaf hydraulic conductivity, plant water usage in response to stress (Vandeleur et al, 2009;Vandeleur et al, 2014;Sade and Moshelion, 2017). Similarly, an observation where an up regulation of ClAQP was observed under salinity and drought stress and also during fruit development of the cultivated watermelon and cucumis melo (Wang et al, 2016;Kusvuran et al, 2021;Lopez-Zaplana et al, 2022) suggesting the involvement of the aquaporins in tolerance mechanisms of the citrullus species. Another important protectant that has been documented to play an important role in drought and salinity stress is the trehalose that is suggested to play an important role in regulation of stomatal aperture, regulation of plant water use, osmolyte protectants and acting as an energy source thus aiding the tolerance mechanisms of plants.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 75%
See 1 more Smart Citation
“…In their role against drought and salinity stresses, it has been suggested that the Aquaporins regulated changes in the root, stem and leaf hydraulic conductivity, plant water usage in response to stress (Vandeleur et al, 2009;Vandeleur et al, 2014;Sade and Moshelion, 2017). Similarly, an observation where an up regulation of ClAQP was observed under salinity and drought stress and also during fruit development of the cultivated watermelon and cucumis melo (Wang et al, 2016;Kusvuran et al, 2021;Lopez-Zaplana et al, 2022) suggesting the involvement of the aquaporins in tolerance mechanisms of the citrullus species. Another important protectant that has been documented to play an important role in drought and salinity stress is the trehalose that is suggested to play an important role in regulation of stomatal aperture, regulation of plant water use, osmolyte protectants and acting as an energy source thus aiding the tolerance mechanisms of plants.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 75%
“…Cultivated watermelon has been recorded to be salt sensitive and thus attempts to improve the crop has primarily focused on the use of salt tolerant roots stocks to graft the crop. Watermelon showed great resistance to salinity when grafted to the salt tolerant species which develop a well-established root biomass that aided the grafted plants to accumulate less salt ions thus water uptake was not limited ( Yan et al., 2018 : Zhu et al., 2018 ; Kuşvuran et al., 2021 ). This shows that improvement into the root system (be it morphological, physiological or molecular) will enhance the salinity tolerance of cultivated watermelon.…”
Section: Morpho-physiological Responses To Environmental Stressmentioning
confidence: 99%
“…Были проведены исследования, посвященные изучению устойчивости к солевому стрессу и механизма устойчивости девяти стародавних сортов дыни из Синьцзяна, Китай [25]. Установлено, что при прививке дыни SCP-1 на солеустойчивый подвой дыни TLR-1 значительно уменьшалось повреждающее воздействие, вызванное солевым стрессом, за счет снижения поглощения Na и Cl, что увеличило поглощение Ca и K. Результаты показали, что прививка восприимчивых к соли растений на солеустойчивый подвой улучшала рост растений [26].…”
Section: Introductionunclassified
“…Today, one of the greatest challenges faced by the agriculture and food industries is developing sustainable and environmentally friendly systems to meet the nutritional demand of the continuously growing global population. One of the solutions that would enable producers to increase crop yields and protect produce is the implementation of eco-friendly treatments [20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%